PENDAPAT ULAMA TENTANG KEBOLEHAN BUNGA BANK MENURUT K.H ABDURRAHMAN WAHID (STUDI DI KABUPATEN KETAPANG) - NIM. A1011201284, FITRI IMANDA PERMATASARI (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractThis research is motivated by the use of the interest system in conventional banks. Bank interest has become a spotlight among scholars in Indonesia, some say halal, haram, and subhat. Even the Indonesian Ulema Council has issued a fatwa on bank interest included in the category of usury. However, some scholars still argue that bank interest is allowed. One of the respected figures in Indonesia and has excellent Islamic knowledge, K.H Abdurrahman Wahid, stated that bank interest is allowed. According to him, the use of bank interest in conventional banks is not forbidden usury but a form of business profit sharing that is permitted in Islam. The formulation of the problem in this study is